The Renaissance of Transcervical Balloon Catheters for Cervical Ripening and Labour Induction - Rath, W.; Kehl, S. (Geburtshilfe und Frauenheilkunde, 2015)
Abstract Due to rising rates of labour induction in industrialised countries, safe and effective methods of induction have once again become a focus of interest and research. Prostaglandins are effective for cervical ripening and induction of uterine contractions. They do, however, cause overstimulation of the uterus in up to 20 % of cases, sometimes causing changes in fetal heart rate. Transcervical balloon catheters provide an alternative to prostaglandins for labour induction and have been used for this purpose for almost 50 years. This induction method has experienced a recent renaissance in clinical practice that is reflected in an annually rising number of publications on its use. Balloon catheters allow gentle ripening of the cervix without causing uterine overstimulation. The two catheters available are the Foley catheter (off-label use) and the double balloon catheter, which is licensed for use in induction of labour. Both are as effective as prostaglandins, and do not increase the risk of infection to mother or child. Catheter induction also requires less monitoring compared to prostaglandins resulting in improved patient satisfaction. Balloon catheters provide a useful and promising option to achieve vaginal delivery despite failed prostaglandin induction. Intravenous oxytocin is nevertheless required in up to 85 % of cases for adequate induction/augmentation of contractions. Balloon catheters, vaginal PGE 2 and misoprostol are equally effective in the context of an unripe/unfavourable cervix, the rate of uterine hyperstimulation being significantly lower, and the need for oxytocin significantly higher for catheters. Balloon catheters are increasingly being used in combination or sequentially with oral/vaginal misoprostol, although there is currently inadequate published data on the subject. International guidelines recommend the use of balloon catheters for labour induction with an unripe cervix (also following previous caesarean section) as an alternative to prostaglandins, particularly when these are not available or are contraindicated.